Impact of Distillery Spentwash on the Nutrients of Leaves Vegetables: An Investigation - Basavaraju, H.C.; Chandraju, S. (Asian Journal of Chemistry, 2010)
A field experiment was conducted during summer season Dec-2006 to study the impact of distillery spentwash on the nutrients of different leaves vegetables. The distillery spentwash i.e., primary treated spentwash (PTSW), 50 and 33 % distillery spentwash were analyzed for their physical and chemical parameters. Experimental soil was tested for its chemical and physical parameters. The leaves vegetable seeds (Nanadhari and Mayhco) were sowed in the prepared land dimension of 3' × 4' blocks. Seeds were irrigated by using raw water (RW), 50 and 33 % distillery spentwash. The impact of distillery spentwash on proximate principles (moisture, protein, fat, fibre, carbohydrate, energy, calcium, phosphorous and iron), vitamin content (carotene and vitamin C), mineral and trace elements (magnesium, sodium, potassium, copper, manganese, zinc, chromium and nickel) were studied.